Simultaneous Transcranial Magnetic Stimulation and Functional Magnetic Resonance Imaging: Aspects of Technical Implementation - Caparelli, Elisabeth C.; Zhai, Tianye; Yang, Yihong (Frontiers in Neuroscience, 2020)
The simultaneous transcranial magnetic stimulation (TMS) and functional magnetic resonance imaging (fMRI) offers a unique opportunity to non-invasively stimulate brain circuits while simultaneously monitoring changes in brain activity. In order to take advantage of this multimodal technique, some technical aspects need to be addressed. In this work we evaluated potential technical issues associated with the setup and utilization of this multimodal tool, such as the use of a large single-channel radio frequency (rf)-coil, and the artifacts induced by TMS when interleaved with the echo-planar imaging (EPI) sequence. We demonstrated that good image quality can be achieved with this rf-coil, and that the adoption of axial imaging orientation in conjunction with a safe interval of 100 ms, between the TMS pulse and imaging acquisition, is a suitable combination to eliminate potential artifacts when using the combined TMS-fMRI technique in 3 Tesla MRI scanners.